Comparative statistical analysis of industrial development in post-Soviet countries for the period 1990–2021 - Petrovskaya, Maria Vladimirovna; Tsypin, Alexander Pavlovich; Sharykina, Elsa Anatolyevna (Известия Саратовского университета. Новая серия: Серия «Экономика. Управление. Право», 2023)
Introduction. Despite the transition of economic systems to a digital economy, today industry is a driver of the development of the economy of any country, and accordingly, consideration of the development peculiarities of this sphere in post-Soviet countries is of scientific interest. Hence, the purpose of the study is to analyze the industry development dynamics in the post-Soviet countries in the period of 1990–2021. Materials and methods. In the course of the study, methods such as analysis and synthesis, tabular and graphical, relative and average values were used. Results. At the start of the market transformation, post-Soviet countries had high industrial potential, while the share of the GVA industry in the GDP of each subject was above 20%. As we move away from 1990, more post-Soviet countries are showing a tendency to reduce the GVA ratio, which is due to the combination of factors, the main of which is the impact of the transformational transition and subsequent crises. The best results in hydrocarbon production are shown by countries with natural resource deposits: Russia, Kazakhstan, Azerbaijan and Turkmenistan, the rest of the post-Soviet countries have near-zero production indicators, which reduces their ability to invest “petrodollars” in other sectors of the economy. Indirectly, the import structure shows problems in the manufacturing industry, in which in 2021 the import of machinery and equipment prevails in almost all post-Soviet countries. Conclusions. Summarizing the results obtained during the study, we can draw a general conclusion based on the results of the analysis: having some accumulated (formed) capital in industry, the post-Soviet countries were unable to convert it into sustainable development of their economic systems and at the moment are largely forced to rely on imports of machinery, equipment and vehicles. The findings will be useful to researchers in the field of post-Soviet countries’ integration and disintegration